Modeling different behaviors in disclosing risk perception. Issue 5 (20th February 2020) - Colombi, Roberto; Giordano, Sabrina
Abstract: In many fields, people are requested to express their level of awareness about some risk (mainly associated with health, environment, energy, etc.) by selecting a category in an ordered scale. We propose a model for such ordinal data by taking into account that the observed response does not necessarily reflect the respondent's true opinion since the final answer can be inaccurate or completely random. The proposed model hypothesizes three behaviors in the process of answering: accurate interviewees express their risk perception exactly, uncertain ones randomly select the response according to the uniform distribution, and inaccurate interviewees make evaluation errors but with high probability they choose a rating close to the true one. Statistical inference for the proposed models is addressed without assuming that the model, to be fitted, is correctly specified. Two real case studies on the awareness of geo‐hydrological risk and work‐related stress risk are considered using the proposed methodology.